Pengaruh Strategi Pembelajaran Inovatif Directed Reading and Thinking Activity (DRTA) dan Motivasi Belajar terhadap Kemampuan Membaca Bahasa Inggris Siswa - Yuliana M. D. K. Kara; Maksimilianus Doi (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
Abstract: This study aimed at investigating the ability to read English with DRTA learning strategies and the influence of the interaction between learning strategies and learning motivation on English reading skills. This research is a quasi-experimental study with a 2 x 2 factorial design. The population of the study was 60 students with 2 intact classes and the samples were taken randomly. The technique of collecting data was a test and non-test technique. The data were analyzed using descriptive and inferential statistical techniques. The inferential technique used was the two-way analysis of variance (ANOVA) technique with a significant level of 0.05%. The normality test adopted the Shapiro-Wilk and the homogeneity test used the Levene test and the analysis was continued using t-test. The results show that there is a significant difference in student's ability between DRTA and conventional learning strategies with a significance level of <0.5 (0.08 <0.5). Meanwhile, there is a very significant interaction between motivation and reading ability with a different value of 0.000 <0.5. From the results of this study, it can be concluded that the DRTA learning strategy is more effective than the conventional learning strategy, and there is a motivational effect on students' reading ability in learning English.